Coordination as showcasing: the establishment of Norway's Afghanistan Forum. Issue 3 (3rd July 2019) - Ekhaugen, Lene
ABSTRACT: In complex operations such as the interventions in Iraq and Afghanistan, where multiple government ministries are involved in putting together a state's contributions, the use of national-level coordination bodies has become more widespread. Research has taken for granted that the rationale behind these bodies reflects their declared aim – enhanced coordination as a means to improve mission effectiveness. However, they appear to have had modest effect on coordination. That notwithstanding, they seem to remain popular. This prompts us to ask why such bodies are actually established. This article – based on in-depth interviews and archival records – critically explores the establishment of Norway's ad hoc, inter-ministerial, political-level Afghanistan Forum. Distinguishing between a structural-instrumental, a cultural-institutional and an environmental perspective from organizational theory to structure the analysis, this article shows that the declared purpose of the forum, inter-ministerial coordination, proved less important than showcasing coordination efforts and keeping the coalition together. In addition, national traditions in handling coordination challenges in the central government apparatus and powerful international reforms helped bring the forum about. This has implications for research on the rationale and effectiveness of these bodies, and also for understanding their policy relevance.